Engaged Scholarship and the Ukraine-Russia War (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2023)
ESJ’s managing editor Penelope Sanz converses with Dr. Natalia Khanenko-Friesen, director of the Canadian Institute of Ukrainian Studies (CUIS) at University of Alberta, about engaged scholarship in the context of the Ukraine-Russia war. Natalia was in the midst of organizing and preparing for a conference in Spring 2023 when this conversation took place.